Profile and Factors Associated with Depression, Anxiety, and Stress in Indonesian People During COVID-19 Pandemic - Argo, Teresa Mika; Kurniawan, Andree; Liem, Jean Andrina; Sugianto, Jeremy Octavian; Michael, Rafael Jonathan; Tanuwijaya, Nathania Victoria Stevina; Agatha, Lisa; Wonsono, Beverley; Rivami, Dwi Savitri (Medicinus, 2021)
Background : As a result of the COVID-19 pandemic, Indonesia implemented various policies to break the chain of transmission of COVID-19, starting from large-scale social restrictions, quarantines, and even lockdowns. Without exception, schools were also closed. These conditions affect people psychologically, including levels of depression, anxiety, and stress in students. The aim of this study is to determine profile and factors associated with depression, anxiety, and stress in Indonesian people during the COVID-19 pandemic.Methods : A cross-sectional study among students in Indonesia was conducted to determine depression, anxiety, and stress levels in adolescents based on their sociodemographic characters. The DASS-21 questionnaire was distributed online.Results : A total of 913 people participated from all provinces in Indonesia. Depression, anxiety, and stress were found in 43.5%, 43.3%, 25.2%, respectively. The severity of depression was significantly associated with age (p<0.001), gender(p=0.003), and region(p=0.039). Adults (25-55) are 4.6 times odds more likely to have depression than adolescent during pandemic (OR=4.641, 95% CI=2.053-10.491). The severity of anxiety was significantly associated with age (p=0.002), gender(p<0.001), education (p=0.004) and region(p=0.004). The severity of stress was significantly associated with gender (p<0.001) and education (p=0.018).Conclusion : Depression, anxiety and stress quite common found in Indonesian during COVID-19 pandemic. Several sociodemographic factors were associated with depression, anxiety and stress among Indonesia